1995
DOI: 10.2134/jpa1995.0594
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Planting Date on Canola and Crambe Production

Abstract: Increased interest in alternative sources of oil for edible and industrial uses have stimulated interest in the producti on of new oilseed crops. Spring sown canola (Brassica napus L. and Brassica campestris L.) and crambe (Crambe abyssinica Hochst) have excellent potential to expand the diversity of agricultural crops available to North Dakota producers. The three species are cool season oilseed crops that are adapted to this area. "Canola" is a tradename for varietie of rapeseed from which the oil can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 10 publications
6
38
0
Order By: Relevance
“…The length of the vegetative growth period (emergence to 50% flower) did not differ among seeding dates when averaged across the fallow and stubble sites. In other studies, the number of days from planting to first flower appearance was greater with canola planted in mid-to late April and the first 2 wk of May rather than the last 2 wk of May (Gross 1963;Degenhardt and Kondra 1981;Johnson et al 1995). However, seeding date had minimal effects on the duration of flowering and reproductive periods (Degenhardt and Kondra 1981; Johnson et al 1995).…”
Section: Mid-season Plant Developmentmentioning
confidence: 90%
See 2 more Smart Citations
“…The length of the vegetative growth period (emergence to 50% flower) did not differ among seeding dates when averaged across the fallow and stubble sites. In other studies, the number of days from planting to first flower appearance was greater with canola planted in mid-to late April and the first 2 wk of May rather than the last 2 wk of May (Gross 1963;Degenhardt and Kondra 1981;Johnson et al 1995). However, seeding date had minimal effects on the duration of flowering and reproductive periods (Degenhardt and Kondra 1981; Johnson et al 1995).…”
Section: Mid-season Plant Developmentmentioning
confidence: 90%
“…Researchers in North Dakota also observed that canola seedlings were able to tolerate temperatures of -6°C without significant reductions in plant stand (Johnson et al 1995). However, frost caused significant damage to fall-seeded canola at another location, not included in this portion of the overall study, in 1998 (unpublished data).…”
Section: Emergence and Seedling Densitymentioning
confidence: 94%
See 1 more Smart Citation
“…Drought and salinity stresses are the major limitations for plant growth in arid and semi-arid regions (Huzsvai and Rajkai, 2009). Previous studies noted greatly reduced canola yields due to high temperature and severe drought stress (Johnson et al, 1995). On the other hand, according to Nielsen (1997), canola yield is not significantly affected by water stress at any particular growth stage.…”
Section: Introductionmentioning
confidence: 98%
“…Canola seeded relatively early can also avoid stressful hot and dry periods during flowering that can reduce yield and quality (Johnson et al 1995). However, early spring seeding (e.g., late April or early May) can sometimes be hindered by late snowmelt in the Peace River region.…”
mentioning
confidence: 99%